2009
DOI: 10.1593/neo.09418
|View full text |Cite
|
Sign up to set email alerts
|

LMO2 Is a Novel Predictive Marker for a Better Prognosis in Pancreatic Cancer

Abstract: LMO2 is a promising marker for predicting a better prognosis in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Recently, molecular biomarkers such as RhoA expression, LMO2 expression, or Skp2 expression have also been suggested as novel predictive markers for pancreatic carcinoma [21,22,23]. We have reported that the KRAS mutation predicts poor survival in patients with pancreatic cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular biomarkers such as RhoA expression, LMO2 expression, or Skp2 expression have also been suggested as novel predictive markers for pancreatic carcinoma [21,22,23]. We have reported that the KRAS mutation predicts poor survival in patients with pancreatic cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…The role of LMO2 as oncogene in T-ALL 6 and, conversely, as favorable prognostic factor in DLBCL, 8 CML 9 and pancreatic cancer, 10 led us to evaluate the practically unexplored role of LMO2 in B-ALL. We found that LMO2 is expressed in this disease, as previously proposed.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Full clinical and laboratory data were available for 39 T-ALL and 145 B-ALL patients (one of them lacking survival data) with a median age of 11.5 years (range 0.5-87 years), including 100 children under 15 years of age (median 5.5 years, range 0. [5][6][7][8][9][10][11][12][13][14] and 84 patients over 15 years of age (mean age 34.5, range 15-87). Sample collection was approved by the individual institutional review boards of the participating institutions and informed consent was obtained from all adult patients and children's parents or legal guardians.…”
Section: Patients' Samples and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from FFPE tissue samples using the RNeasy FFPE kit (Qiagen, Tokyo, Japan) with some modification to the manufacturer's instructions after macrodissection based on a review of representative hematoxylin and eosin-stained slides as described previously (19). Total RNA was extracted from cells isolated by microdissection according to the standard acid guanidinium thiocyanate-phenol-chloroform protocol (20), with or without glycogen (Funakoshi, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%